Acute impact of transcatheter edge-to-edge repair for mitral regurgitation on left ventricular function. (3rd October 2022) - Kassar, M; Madhkour, R; Praz, F; Hunziker, L; Windecker, S; Brugger, N
Abstract: Introduction: Transcatheter Edge-to-Edge repair (TEER) for the therapy of mitral valve regurgitation (MR) is an alternative to surgery for high risk patients. It is a minimal invasive procedure but the acute impact of the pre- and afterload decrease, due to the reduction of both MR and mitral valve area (MVA), on the left ventricle (LV) systolic function was never formally evaluated. Method: Fifty patients with mixed MR etiologies from our TEER register with complete 3D datasets of the LV before and after TEER were included in this study. LV volumes and function, as evaluate by ejection fraction (LVEF), global longitudinal strain (LV-GLS) and global circumferential strain (LV-GCS), and the MR (3D vena contracta area, 3D VCA) were evaluated before and at the end of the therapy. Results: The majority of patients suffered from secondary MR (54%), one TEER device was implanted in 64% and two in 36% of the population. TEER leads to a significant reduction of all the LV volume and function parameters excepted for the end-diastolic volume which increased non-significantly (Table 1). The decrease of the LVEF was linked to a decrease of both GLS and GCS in a multivariate analysis (r 0.85), the decrease of GCS having a higher influence (beta −0.606 vs −0.435). In the univariate linear analysis, the reduction of LVEF, GLS and GCS were inverse proportional to the LVEF before TEER and direct proportional to the reduction of the 3D VCA. LVEF decrease was also directly linked to MVA percental reduction. After multivariate evaluation, LVEF reduction kept linked to LVEF before TEER and VCA 3D reduction (r=0.51, p=0.001), GCS decrease only to VCA 3D reduction (r=0.371, P=0.08) and GLS diminution only to LVEF before TEER (r=0.313, p=0.027). Conclusion: After TEER, left ventricular function reduction seems principally linked to the afterload increase (i.e. the MR reduction); the circumferential function and the left ventricles with the highest ejection fractions being apparently maximally impacted. Funding Acknowledgement: Type of funding sources: None.